The Effect of Islamic Corporate Governance Disclosure and Operational Efficiency on Financial Sustainability in Islamic Commercial Banks in Indonesia for the 2020–2024 Period - Elsa Shifa Alfitriani; Romli Romli (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aimed to analyze the effect of Islamic Corporate Governance Disclosure and operational efficiency on Financial Sustainability in Islamic Commercial Banks in Indonesia during the 2020–2024 period. This study used a quantitative approach with secondary data obtained from annual reports and financial statements of 12 Islamic Commercial Banks. The sampling technique used was saturated sampling with a total of 60 observations. Data analysis was conducted using multiple linear regression analysis with IBM SPSS Statistics 31. The results showed that Islamic Corporate Governance Disclosure had a positive but insignificant effect on Financial Sustainability. Meanwhile, operational efficiency had a positive and significant effect on Financial Sustainability. Simultaneously, both variables did not significantly affect Financial Sustainability. These findings indicate that operational efficiency plays a more important role in improving sustainable financial performance in Islamic banks. Therefore, Islamic Commercial Banks are expected to improve operational efficiency to maintain long-term financial sustainability.